Odpowiedzi

2010-04-11T17:03:53+02:00
A
6-4y+12=22
-4y=22-6-12
-4y= 4|:-4
y=-1

b
0,8(2x-1)+0,3(4-5x)=0
1,6x- 0,8+1,2-1,5x=0
0,1x= 0,4|:0,1
x= 4

c
15z+3(1-2z)=9z
15z+3-6z=9z
0=-3

d
-0,8(3z-8)-5(0,4-2z)=2(3,8z+2,2)
-2,4z+6,4-2+10z=7,6z+4,4
0= 0

chyba dobrze..
tylko tyle wiem;(
1 2 1
Najlepsza Odpowiedź!
2010-04-11T17:08:26+02:00
Zad 17
a) 6-4(y-3)=22
6-4y+12=22
6-4y=10
-4y=4
4y=-4
y=-1

b) 15z+3(1-2z)=9z
15z+3-6z=9z
15z+3=15z
15z=15z+3
0=3

c) 1,6-0,8+1,2-1,5x=0
16x-8+12-15z= 0
x+12=8
x=-4

zad.18
a) 2x/3+3x/4+4x/5= -2(-x+1)-1/6 / *60
40x+45x+48x= 120x-120-10
133x= 120x - 130 / - 120x
13x= -130
x= -10
2 4 2